2021
DOI: 10.1021/acssuschemeng.0c08586
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids–Cobalt(II) Thermochromic Complexes: How the Structure Tunability Affects “Self-Contained” Systems

Abstract: With the aim of obtaining thermochromic systems with potential applications in solar energy storage, we evaluated the behavior of some sugar-based ionic liquids (ILs)−Co(NTf 2 ) 2 complexes, in IL solution, as a function of temperature. Different structural changes on the cation, the nature of the anion, and the nature of the IL used as the solvent were considered. The analysis of the above factors was carried out through a combined approach of different techniques, that is, variable temperature UV−vis and NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…150 ppm/°C Δδ/Δ T for the 59 Co nucleus is larger than all other reported systems, many by at least an order of magnitude (Figure ). For example, the typical temperature dependence of the 59 Co NMR shift is between 1 and 3 ppm/°C, with the highest for a Co­(III) complex belonging to Co­(acac) 3 (acac = acetylacetonate) at 3.15 ppm/°C. , Relatively recently, a higher temperature dependence was reported for a putative Co­(II) complex at 8.5 ppm/°C . The complexes here eclipse all of those.…”
Section: Resultssupporting
confidence: 46%
See 1 more Smart Citation
“…150 ppm/°C Δδ/Δ T for the 59 Co nucleus is larger than all other reported systems, many by at least an order of magnitude (Figure ). For example, the typical temperature dependence of the 59 Co NMR shift is between 1 and 3 ppm/°C, with the highest for a Co­(III) complex belonging to Co­(acac) 3 (acac = acetylacetonate) at 3.15 ppm/°C. , Relatively recently, a higher temperature dependence was reported for a putative Co­(II) complex at 8.5 ppm/°C . The complexes here eclipse all of those.…”
Section: Resultssupporting
confidence: 46%
“…17,28 Relatively recently, a higher temperature dependence was reported for a putative Co(II) complex at 8.5 ppm/°C. 29 The complexes here eclipse all of those. A preliminary study of 2 in a 300 MHz NMR showed 131 ppm/°Cand our results here, which are even higher, suggest amplification of T sensitivity with the higher magnetic field.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Understanding how to deliberately design and manipulate thermochromic materials has driven technological innovation and progress for numerous applications requiring thermally sensitive smart glasses, temperature probes, and sensors, among others. Materials with thermochromic properties are more likely to be commercially viable when the thermochromic transitions exhibit large spectral shifts, reversibility, and discreteness (i.e., occurring at a well-defined temperature). ,, Here, we investigate the metal- dieten ( N , N -diethylethylenediamine) family of compounds (e.g., [M­( dieten ) 2 ]­(X) 2 , where M = Cu 2+ , Ni 2+ and X = certain monovalent anions) as they exhibit those important thermochromic characteristics while also possessing tunable molecular properties and interactions that govern their thermochromic behavior. , …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, extensive research on ionic liquids has been conducted in numerous fields, such as electrochemistry and organic synthesis. Ionic liquids are typically onium salts, although various functional ionic liquids containing metal complexes have been synthesized in recent years. Our laboratory has synthesized several ionic liquids containing cationic sandwich or half-sandwich complexes, which exhibit unique functionalities such as magnetism, chemical reactivity, and stimuli-responsiveness in addition to ionic conductivity. …”
Section: Introductionmentioning
confidence: 99%